Intersectional elaboration: Using a multiracial feminist co-design technique with Latina teens for emotional health. (April 2022) - Vacca, Ralph
Underlying the growing epidemic of mental distress and suicidal ideation amongst certain marginalised groups (e.g. Latina teens) are complex intersections of ecologies and interrelated structures of inequality such as class, culture, race and gender. Through the use of a multiracial feminist framework, the proposed intersectional elaboration technique examines how technology might be designed in ways that explicitly consider intersecting structures of inequality and eco-developmental contexts. The core of this technique involves co-constructing narratives using prompts that directly address specific layers of one's ecology and the interactions across ecological layers – purposely addressing intersecting systems of inequality acting along these ecologies. This article describes the application of the intersectional elaboration technique in co-design research with adolescent Latinas, in a highly urbanised context, towards designing emotional health technology. Findings suggest that intersectional elaborations can serve as a useful generative co-design technique to inform designs that address complex arrangements of intra-ecological conflicts and cultural legitimacy.